An interaction field model for immiscible fluids - Brown, Richard Ewart (My University, 2016)
An alternative to the classical surface tension model is proposed for the engineering analysis ( abbreviation of abstract )
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, South Africa for the degree of Doctor of Philosophy, Johannesburg 1996